INVESTIGATION OF HYPOLIPIDEMIC EFFECT OF SESQUITERPENE Γ-LACTONE AHILLIN IN HEPATOMA TISSUE CULTURE (HTC) CELLS - V. V. Ivanov; A. V. Ratkin; Yu. A. Pfarger; O. A. Kaidash; N. V. Ryazantseva; S. M. Adekenov; V. S. Chuchalin (Бюллетень сибирской медицины)
Objective. Investigation of hypolipidemic effect of sesquiterpene γ-lactone ahillin in hepatoma tissue culture (HTC) cells.Material and methods. In this study we’ve evaluated the effect of γ-lactone sesquiterpene aсhillin and gemfibrozil (comparator drug) on the lipid content in the hepatoma tissue culture (HTC) cell which were incubated with a fat emulsion lipofundin by fluorescent method with vital dye Nile Redand staining the cells with the dye Oil Red O. The cell viability was investigated using the MTT-test and staining with Trypan blue.Results. Cultivation cells HTC with aсhillin and gemfibrozilat concentrations ranging from 0.5 to1.5 mM and from0.25 mM to0.5 mM, respectively, resulted in dose-dependent decrease of the fluorescence’s intensity Nile Red. It reflects a decrease in lipid content in the cells. At these concentrations the drugs didn’t have cytotoxic effect and the cell viability didn’t change compared to the control culture.An experimental hyperlipidemia in the hepatoma culture cells was induced by adding to the incubation medium a fat emulsion lipofundin at a final concentration 0.05%. The intensity of fluorescence Nile Red in the cells was increased 4 fold (p < 0.05). This result suggests the significant accumulation of lipids in the cell’s cytosol and confirmed by microscopy after staining neutral lipids with the dye Oil Red O. Under these conditions aсhillin and gemfibrozil reduced lipid content in cells and hadthe effect at concentrations of0.5 mM and0.25 mM respectively.Conclusion. In the lipofundin-mediated model of hyperlipidemia the sesquiterpene lactone aсhillin prevents the lipid accumulation in cells. It confirms by decrease of fluorescence Nile Red and reduction lipid drops which were stained with Oil Red O in cytosol. To establish the molecular targets of aсhillin’saction on lipid metabolism in cell culture HTC we need to investigate a gene expression of key enzymes of lipid metabolism.